Effects of Tillage Systems on the Physical Properties of Soils in a Semi-Arid Region of Morocco - Abdelali El Mekkaoui; Rachid Moussadek; Rachid Mrabet; Ahmed Douaik; Rachid El Haddadi; Outmane Bouhlal; Mariyam Elomari; Matike Ganoudi; Abdelmjid Zouahri; Said Chakiri (Agriculture, 2023)
Climate change, drought, erosion, water contamination resources, desertification, and loss of soil quality represent major environmental risks worldwide. Facing these risks is the most important issue for sustainable development. Conventional tillage (CT) practices seem to expose the soils of semi-arid regions, which are initially fragile, to degradation that is accentuated by the overuse of the environment. The benefits of conservation agriculture (CA) could mitigate the degradation of natural resources, particularly soils. The adaptation and transfer of the no-till (NT) system with mulch open new perspectives for the development of agriculture in semi-arid regions. The main objective of this study is to assess the impact of conservation agriculture, especially no-till (NT) system, on the physical properties of soil (structural stability (SS), bulk density (BD), gravimetric water content (θg), and soil organic matter (SOM)) compared to conventional tillage (CT). The main changes associated with the transition from a CT system to an NT system were evaluated at the experimental site, Merchouch (M13), which is typified by vertisol soil, and at the Ain Sbit (AS7) site, which is characterized by isohumic soil. Under a no-till system, most of the physical properties of the soil were improved in both sites, with a clear difference in the M13 site. Structural stability under NT showed a significant increase in both sites (fast wetting (FW), slow wetting (SW), and wet stirring (WS) improved by 88, 43, and 83% at the M13 site, respectively, against, 16, 23, and 7%, respectively, at the AS7 site). On the other hand, the SOM increased from 2.0 to 2.6% (an improvement of 28%) at AS7 and from 1.2% to 1.9% (an improvement of 52%) at M13. This research demonstrated that conservation agriculture, especially NT, improves the soil physical quality in both medium and long terms, confirming its suitability for the climatic and edaphic constraints of semi-arid areas in Morocco as well as in other parts of the world.